CHILD INFECTIONS AND IMMUNIZATION PROBLEMS IN ADULTS. EXPERIENCE OF THE FAMILY VACCINAL PREVENTION CENTER - M. G. Galitskaya; L. S. Namazova-Baranova; N. E. Tkachenko; M. V. Fedoseenko; V. V. Botvinyeva; F. C. Shakhtatinskaya (Педиатрическая фармакология)
The article is dedicated to the vaccination issues of the adult population. The authors list the main factors conditioning the problem's relevance. The given material reflects the experience of foreign colleagues and cites the authors' observations. The amount of people vaccinated at the family vaccinal prevention Center of the RAMS FSBI "SCCH" from January 2010 and July 2012 thanks to the active health communication offered by the Center's personnel is as follows: against hepatitis B - 118, against hepatitis A - 121, against chickenpox - 92 adult patients. According to the authors, this category of patients is being actively immunized against influenza and pneumococcal infection. An important role in the article is given to the cervical carcinoma prevention. 2,352 vaccinations against the human papilloma virus were made at the Center in 2007-2011. The authors analyzed the motivation of the vaccinated patients and proved the role of public awareness measures. The article discloses the role and prospects of family vaccination and shows the need for regulatory legal measures in order to change the current unregulated vaccination tendencies in the adult population.